2018
DOI: 10.1002/mrm.27576
|View full text |Cite
|
Sign up to set email alerts
|

UTE‐SENCEFUL: first results for 3D high‐resolution lung ventilation imaging

Abstract: Purpose This study aimed to develop a 3D MRI technique to assess lung ventilation in free‐breathing and without the administration of contrast agent. Methods A 3D‐UTE sequence with a koosh ball trajectory was developed for a 3 Tesla scanner. An oversampled k‐space was acquired, and the direct current signal from the k‐space center was used as a navigator to sort the acquired data into 8 individual breathing phases. Gradient delays were corrected, and iterative SENSE was used to reconstruct the individual timef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Quantitative assessment of lung aeration based on MRI has been very limited, mainly because of technical challenges of MR imaging (Ball et al, 2017b), for example, the prolonged time required for image acquisition, and the low proton density within the lung parenchyma. However, recent experimental data, ex vivo (Ball et al, 2018) and in-vivo (Kuethe et al, 2018) have suggested that lung MRI may be feasible and produce clinically valuable information (Ozcan et al, 2017), including functional imaging (Mendes Pereira et al, 2018). Ball et al observed in ex-vivo pig lungs that lung density was a linear function of MRI T2 signal intensity normalized to muscle intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative assessment of lung aeration based on MRI has been very limited, mainly because of technical challenges of MR imaging (Ball et al, 2017b), for example, the prolonged time required for image acquisition, and the low proton density within the lung parenchyma. However, recent experimental data, ex vivo (Ball et al, 2018) and in-vivo (Kuethe et al, 2018) have suggested that lung MRI may be feasible and produce clinically valuable information (Ozcan et al, 2017), including functional imaging (Mendes Pereira et al, 2018). Ball et al observed in ex-vivo pig lungs that lung density was a linear function of MRI T2 signal intensity normalized to muscle intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The measured data were binned into partially overlapping breathing states, with the requirement that all breathing states contain about 21% of all acquired data. The respiratory cycle was resolved in eight breathing states, which is a typical range for dynamic 3D lung acquisitions 7,15 . This approach ensures that all k‐space bins (corresponding to the breathing states) contain a sufficient amount of data for a stable parallel imaging reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the center of k‐space can be exploited as a navigator signal 4‐6 . Although some non‐Cartesian k‐space trajectories inherently measure this (direct current) DC signal in each repetition, 7 a small increase in measurement time has to be invested in Cartesian and in wave‐CAIPI (controlled aliasing in parallel imaging). The big advantage of these self‐gating techniques is that they do not require any additional hardware, which saves time during patient preparation and increases patient comfort.…”
Section: Introductionmentioning
confidence: 99%
“…External respiratory belts are widely used to indirectly track the motion by measuring the respiratory-induced abdomen stretching. An alternative way is to use the repeatedly acquired k-space center (DC), which is feasible for center-out UTE sequences, measuring the signal change caused by respiratory motion 7,11,13,14 . To more accurately and directly characterize subject motion, low spatial but high temporal resolution 2D/3D images could be reconstructed and used as a self-navigator 6,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%